2022
DOI: 10.1155/2022/7556315
|View full text |Cite
|
Sign up to set email alerts
|

The Diagnostic Value of 18F‐FDG PET/CT Bone Marrow Uptake Pattern in Detecting Bone Marrow Involvement in Pediatric Neuroblastoma Patients

Abstract: Objectives. To explore the diagnostic value of 18F-FDG PET/CT bone marrow uptake pattern (BMUP) in detecting bone marrow involvement (BMI) in pediatric neuroblastoma (NB) patients. Methods. Ninety-eight NB patients were enrolled in BMI analysis. Four patterns of bone marrow uptake were categorized based on pretreatment cF-FDG PET/CT images. Some crucial inspection indexes and 18F-FDG PET/CT metabolic parameters were analyzed. The BMUP was divided into BMUP1, BMUP2, BMUP3, and BMUP4. Paired-like homeobox 2b (PH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…The bone marrow is the most common site of metastasis in neuroblastoma [ 3 ], and the spread of tumor cells to bone marrow is a grim prognostic factor in neuroblastoma patients [ 4 ]. The prognosis is significantly better in those without bone marrow involvement (BMI) than in those with BMI [ 5 , 6 ]. Moreover, BMI is one of the most important diagnostic criteria and an important risk factor for staging according to the International Neuroblastoma Staging System (INSS) and the International Neuroblastoma Risk Group staging system [ 7 – 9 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The bone marrow is the most common site of metastasis in neuroblastoma [ 3 ], and the spread of tumor cells to bone marrow is a grim prognostic factor in neuroblastoma patients [ 4 ]. The prognosis is significantly better in those without bone marrow involvement (BMI) than in those with BMI [ 5 , 6 ]. Moreover, BMI is one of the most important diagnostic criteria and an important risk factor for staging according to the International Neuroblastoma Staging System (INSS) and the International Neuroblastoma Risk Group staging system [ 7 – 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…According to the recommendations of the INSS, the cytology of aspirates and histology of biopsies are the gold standard with which to assess BMI in patients with neuroblastoma [ 5 , 7 , 8 ]. Considering that most neuroblastoma patients are children, the bone marrow aspirates and biopsies must be performed only by experienced health care providers who have been well-trained in the technique [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…The main reason for this may be that 18F-FDG PET/CT is an integrated imaging modality of PET and CT that can provide both metabolic and anatomical information. [32] In total, 405 patients were included in the risk model. Twenty-three features were selected for submodel 1a and 35 features were selected for submodel 1b.…”
Section: Discussionmentioning
confidence: 99%
“…The main reason for this may be that 18F-FDG PET/CT is an integrated imaging modality of PET and CT that can provide both metabolic and anatomical information. [32]…”
Section: Discussionmentioning
confidence: 99%
“…The ROC curve analyses showed that the AUCs of BM-SUVmax and BM-SUVmax/HE-SUVmax were 0.398 (95% CI: 0.156–0.640; p = 0.456) and 0.582 (95% CI: 0.319–0.844; p = 0.551), respectively, for predicting BMI. The ROC curve analyses cannot distinguish between patterns C and D. 18 F-FDG PET/CT-guided BMB should be performed to reduce the harm of unnecessary BM aspiration biopsies in patients with pattern C ( 23 ).…”
Section: Discussionmentioning
confidence: 99%